2021
DOI: 10.3389/fcomm.2021.617532
|View full text |Cite
|
Sign up to set email alerts
|

Sound-Symbolic Semantics of Written Japanese Vowels in a Paper-Based Survey Study

Abstract: Verbal sounds can be associated with specific meanings, a phenomenon called sound symbolism. Previous findings of sound symbolism have shown that words including specific consonants or vowels or mouth shapes to pronounce specific vowels associate with specific and subjective physical and emotional evaluations. The purpose of this study was to examine whether each written vowel in a given language was individually associated with specific subjective evaluations. Six hundred and thirteen participants used five-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…For example, when participants judge whether the name of a presented meaningless round figure is bouba (malma) or kiki (takete), they consistently choose bouba as the name of the round figure (bouba-kiki effects; Köhler, 1947;Ramachandran and Hubbard 2001;Westbury, 2005;Aryani et al, 2020). In addition, each sound-symbolic word, each written vowel, or each mouth shape to pronounce a vowel is associated with specific, subjective evaluations (perceptual imageabilities and emotional features; e.g., Namba and Kambara, 2020;Ando et al, 2021;Kambara and Umemura, 2021). Future studies should consider the sound-symbolic effects on the associative learning of words and referents.…”
Section: Future Directionsmentioning
confidence: 99%
“…For example, when participants judge whether the name of a presented meaningless round figure is bouba (malma) or kiki (takete), they consistently choose bouba as the name of the round figure (bouba-kiki effects; Köhler, 1947;Ramachandran and Hubbard 2001;Westbury, 2005;Aryani et al, 2020). In addition, each sound-symbolic word, each written vowel, or each mouth shape to pronounce a vowel is associated with specific, subjective evaluations (perceptual imageabilities and emotional features; e.g., Namba and Kambara, 2020;Ando et al, 2021;Kambara and Umemura, 2021). Future studies should consider the sound-symbolic effects on the associative learning of words and referents.…”
Section: Future Directionsmentioning
confidence: 99%
“…In addition to sound-symbolic associations between pseudowords (new words) and referents, real words can be sound symbolically associated with perceptual or abstract features [ 11 , 12 ]. Previous findings suggested that the oral shapes to pronounce linguistic features were associated with perceptual and emotional features [ 5 , 13 ], whereas written linguistic features (alphabetic letters and other characters) were also associated with them [ 14 , 15 , 16 ]. Namba and Kambara (2020) reported that the oral shapes to produce Japanese vowels were connected to specific perceptual and emotional evaluations (e.g., some oral shapes were perceived as bigger, wider, and higher than oral shapes used to produce other vowels) [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sound-symbolic relationships could occur from already acquired associations between linguistic and referential features in native languages [ 27 ]. Other studies also reported that linguistic information was specifically associated with perceptually and emotionally subjective evaluations by using semantic differential scales [ 14 , 28 , 29 , 30 ]. For example, participants differentially evaluated familiarity, visual imageability, auditory imageability, tactile imageability, emotional valence (preference), and arousal (excitement) of sound-symbolic words including voiced consonants and sound-symbolic words including semi-voiced or unvoiced consonants [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations